The Pediatric Dental Pyramid: A Comprehensive Model of Contemporary Factors in Pediatric Dental Care - Setty, Jyothsna V; Shetty, Vidyullatha V; K V, Srikanth; Shilpa S,; Srinivasan, Ila; Jaikrishna, Aparna (Medicine and Medical Research: New Perspectives Vol. 9, 2024)
The success of dental procedures for young patients hinges on several crucial factors. To illustrate these key components, a pyramid model was created. At the top of this pyramid is the child, the central focus of care. Surrounding the child are four fundamental elements: parents, society, the dentist, and e-screens. These elements form the base of the pyramid, highlighting the core influences that impact effective Pediatric dental care. The child's cooperation and behavior, along with the dentist's expertise and skill, are the most crucial factors for achieving successful treatment outcomes. The pyramid consists of five distinct layers, each representing a different level of interaction and emphasizing the importance of various factors in the child's care. The apex of the pyramid features the most critical contributor, with other elements supporting in a hierarchical manner as you move toward the base. The Pediatric Dentistry Management Pyramid provides a clear visual depiction of the interrelationships and relative significance of these factors in achieving optimal patient care. Understanding and addressing each of these components enables a more thorough and effective Pediatric dental practice, ultimately resulting in better treatment outcomes and a more positive experience for both the child and their family.